The Entrepreneurship Dynamic: Origins of Entrepreneurship and the Evolution of IndustriesThe Entrepreneurship Dynamic: Origins of Entrepreneurship and the Evolution of Industries, edited by SchoonhovenClaudia Bird and RomanelliElaine. Stanford, CA: Stanford University Press, 2001. - Eisenhardt, Kathleen M.; Companys, Yosem E. (Academy of Management Review, 2002)
The article reviews the book “The Entrepreneurship Dynamic: Origins of Entrepreneurship and the Evolution of Industries,” edited by Claudia Bird Schoonhoven and Elaine Romanelli.